MEKANISME PENGAWASAN DAN PENGENDALIAN TENAGA SURVEILANS KESEHATAN (GASURKES) PROGRAM KESEHATAN IBU DAN ANAK (KIA) DI DINAS KESEHATAN KOTA SEMARANG - Iwan Yunianto; Ayun Sriatmi; Septo Pawelas Arso (Jurnal Kesehatan Masyarakat (Undip), 2019)
Efforts to accelerate the reduction of maternal mortality rates (AKI) in the city of Semarang have become a serious concern of the Semarang City Government. DKK Semarang has conducted a strategy and effort through empowering midwives as surveillance personnel called Gasurkes KIA. Gasurkes activities play a role in monitoring, data collection and mentoring of pregnant women. Every pregnant woman is expected to receive adequate health services according to her pregnancy condition until the time of delivery and postpartum. Considering that the available data shows  the coverage of pregnant women and postpartum mothers is still low, while the implementation of Gasurkes requires an increase in performance and adequate quality of service so the research on supervision is important. Research on the mechanism of supervision and control of the KIA Gasurkes at the Semarang City Health Office is intended to find out the extent of the current supervision implementation process. This research is an effort to describe the supervision related to the implementation of the KIA Gasurkes in the DKK of Semarang City. By using descriptive qualitative methods, it is expected to be able to display an overview of Gasurkes supervision in the DKK Semarang in actual terms. Research results show that the process of implementing Gasurkes in the MCH program in DKK Semarang has been implemented since the planning process until the implementation of the program. However, the implementation of supervision has not run optimally with still low and unmeasured performance achievement indicators. Repair improvment of supervision by carrying out supervision stages makes it easier  the program to achieve its objectives. Building the concept of a planned supervision mechanism and consistent application of supervision will strengthen the implementation of more adequate supervision. Stages in the supervision include: Setting standards, determining how to measure, measuring results, comparing results to standards and determining corrective actions.